Cytokinin induces expansin gene expression in Melilotus alba Desr. wild-type and the non-nodulating, non-mycorrhizal (Nod - Myc - ) mutant Masym3 - Lee, Angie (2008)
We previously showed that applying 10-6 M of the cytokinin 6-benzylaminopurine (BAP) to uninoculated roots of Masym3, a Nod-Myc- Melilotus alba (Desr.) mutant, resulted in the accumulation of MaENOD40 transcripts to levels similar to BAP-treated wild-type roots.  In contrast, inoculation with a Nod- S. meliloti mutant expressing the trans-zeatin synthase gene of Agrobacterium tumefaciens (Nod-/pTZS+) did not induce MaENOD40 transcript accumulation in either wild-type or Masym3 roots.  However, Masym3 root hairs became swollen at their tips following inoculation with wild-type or Nod-/pTZS+ rhizobia.  Because root hair distention and elongation are often correlated with increased expansin activity, we investigated whether BAP treatment or inoculation with Nod-/pTZS+ S. meliloti up-regulated the expression of expansin mRNAs.  We first determined that treating wild-type roots with 10-5 or 10-6 M BAP resulted in greater MaEXPA1 transcript accumulation than treating roots with comparable concentrations of the auxin NAA.  When Masym3 roots were treated with 10-6 M BAP, MaEXPA1 mRNAs accumulated to levels comparable to wild-type roots.  We then showed that MaEXPA1 mRNAs accumulated in wild-type M. alba roots in response to the Nod-/pTZS+ S. meliloti strain.  Masym3 mutant roots inoculated with Nod-/pTZS+ rhizobia were also up-regulated for MaEXPA1 expression.